2018
DOI: 10.14419/ijet.v7i2.24.12010
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Adaptive Detection of Pulmonary Nodules in Thoracic CT Images Using a Contextual Clustering Based Region Growing

Abstract: For segmenting the Region of interest and for analyzing each area separately to locate whether pathologies present in it or not, we use segmentation process as the first step to diagnose lung image using ComputerAided Diagnosis. In this paper, ROI is segmented by using supervised Contextual Clustering in addition to the Region growing algorithm. Accurate segmentation of the lungs from the chest volume is obtained from the Contextual clustering which is better than all other thresholding approaches that are sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The proposed system was tested on 205 patient cases taken from the openly accessible online LIDC database. The experimental results obtained a sensitivity of 89.2% at 4.14 FPs/scan, and the system was found to be successful [101]. The results of the study showed that the genetic algorithm method developed by Boroczky et al for extracting features from private data obtained from lung CT scans (including 52 real nodules and 443 fake ones) was 100% accurate and 56.4% accurate [102].…”
Section: Classification: False Positive Reductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The proposed system was tested on 205 patient cases taken from the openly accessible online LIDC database. The experimental results obtained a sensitivity of 89.2% at 4.14 FPs/scan, and the system was found to be successful [101]. The results of the study showed that the genetic algorithm method developed by Boroczky et al for extracting features from private data obtained from lung CT scans (including 52 real nodules and 443 fake ones) was 100% accurate and 56.4% accurate [102].…”
Section: Classification: False Positive Reductionmentioning
confidence: 80%
“…Additionally, the test had a sensitivity of 85.91%. Han et al [101] and Boroczky et al [102] carried out yet another investigation in which the SVM method was utilized. In this particular investigation, the classification performed by feature-based SVM was dependent on categorical rules.…”
Section: Classification: False Positive Reductionmentioning
confidence: 99%